Perbedaan Pola Sidik Jari Manusia Menurut Sains dan Tafsir Qur’an Surat Al-Qiyamah Ayat 3-4 - Moch Naufal Ramdhani; Deden Suparman (Moral : Jurnal kajian Pendidikan Islam, 2024)
Knowledge in the field of science is increasingly developing day by day following environmental conditions and human thinking. So science, especially in the field of science, should not be separated from religion. In the Al-Qur'an there are many verses that explain the process of human creation, such as in Surah Al-Hajj verse 5, Surah Al-Mukmin verse 67, Surah Az-Zumar verse 7, Surah Fathir verse 11, and many more. . someone can observe humans through biological observations. In the Qur'an, humans are often called "Basyar", where the word basyar is often compared to the biological characteristics of humans. Fingerprints are polygene inheritance. Based on Galton's system, fingerprints can be divided into 3 basic patterns, namely: curved shape or Arch (A), figure shape or Loop (L), and circle shape or Whorl (W). Finger tendrils can be widely used as a means of identifying a person, biological aspects. Human fingerprints vary from one person to another, even if they are identical twins. Apart from that, it can also be a feature of fingerprints and none of them are exactly the same because they are different from one individual to another.